TYPOLOGICAL AND ICONOGRAPHIC DEFINITION OF A TSHTM COVER WITH UNIQUE CÁSTULO DECORATION (Salduie, 2025)
In this work, the existence of Late Meridional Hispanic terra sigillata (TSHTM) form 17 has been confirmed by the analysis of a piece with a singular decoration. It should be described typologically as a lid. However, the decorative and iconographic study of this lid has been the subject of special attention, taking into account that it is the first truly figurative decoration made in TSHTM using the white slip painting technique. Both the syntactic composition and its different elements have been analyzed on the basis of the three socio-religious groups found in Cástulo in the 5th century AD, the date in which this piece has been contextualized. The comparative study of the iconographic collection used by those social groups allows us to firmly conclude that the iconography of this piece is of a Judeo-Christian character. Although one could venture a more Jewish than Christian profile.
Keywords: Sigillata; Late antiquity; Typology; Pagan; Christian; Jewish; Swastika; Tree of life; Palm tree